EXTH-64. IMIPRIDONES CAUSE METABOLIC REPROGRAMMING AND ELICIT UNIQUE VULNERABILITIES IN PRECLINICAL MODEL SYSTEMS OF GLIOBLASTOMA. (5th November 2018) - Ishida, Chiaki; Zhang, Yiru; Westhoff, Mike-Andrew; Karpel-Massler, Georg; Prabhu, Varun Vijay; Allen, Joshua; Siegelin, Markus
Abstract: The purpose of this study is to improve the efficacy of imipridones, a novel class of AKT/ERK inhibitors. The lead compound ONC201 has entered clinical testing for glioblastoma (GBM) and recently chemically modified imipridones, ONC206 and ONC212, have been designed. Transcriptome, untargeted liquid chromatography/mass spectrometry and extracellular flux analysis unraveled the mechanism of action of novel imipridone compounds, ONC206 and ONC212. We used orthotopic patient-derived GBM xenografts to assess preclinical treatment efficacy. Imipridones inhibit the proliferation of patient-derived xenograft and stem-like glioblastoma cell cultures in vitro and in multiple xenograft models in vivo . ONC212 demonstrated the highest efficacy. High levels of c-myc predict susceptibility to cell death induction by imipridones and increased host survival in orthotopic patient-derived xenografts. At 1h, imipridones inhibit AKT and ERK signaling, accompanied by dephosphorylation of GSK3b. GSK3b phosphorylates c-myc at threonine 58, leading to its proteasomal degradation. Imipridone mediated suppression of c-myc inhibits both glycolysis and oxidative phosphorylation. In turn, energy deprivation leads to a compensatory activation of the serine-one carbon-glycine (SOG) pathway. Interference with the SOG pathway through novel inhibitors of phosphoglycerate dehydrogenase (PHGDH) results in synergistic apoptosis induction in vitro and in vivo . These observations suggest that c-myc expression predicts therapeutic responses to imipridones and that imipridone mediated inhibition of c-myc leads to suppression of tumor cell energy metabolism, eliciting unique metabolic vulnerabilities that can be exploited for clinical relevant drug combination therapies.